Investigations on blowing agents for the processability of foamed parts by rotational molding techniques - Lopes, Joana (2022)
[Excerpt] Polymeric foams consist of two distinct phases, a solid polymer matrix and a gaseous phase produced by the addition of one or more blowing agents. The production capability of polymeric foamed parts represents an important expansion of the range of properties in the plastics industry, and their unique properties broaden the variety of possible applications [1]. The production of polymeric foams is guided by the reduction in material consumption and weight, and their final performance. The density of foamed parts can be considerably reduced (the foams expand between 20 and 300 times), reducing the consumption of the polymeric matrix during processing. This feature is very attractive for industries using expensive materials since the cost of plastics can be up to 70% of the total production cost. [...]